Augmented Reversal of Cisplatin-Induced Delayed Gastric Emptying by Amla (Emblica Officinalis) Fruit Extract in Sprague-Dawley Rats. (3rd September 2018) - Ahmad, Asad; Khushtar, Mohammad; Kumar, Ranjan; Badruddeen,; Riyaz, Ambreena; Khan, Mohammad Irfan; Rahman, Azizur
ABSTRACT: Despite the availability of effective antiemetics, control of acute and delayed chemotherapy-induced nausea and vomiting (CINV) is often suboptimal and there is need of an inexpensive and safer alternative. Thus, this study was designed to evaluate the effect of Emblica officinalis Gaertn (Euphorbiaceae) fruit extract (EEEO) on cisplatin-induced delayed gastric emptying in Sprague-Dawley rats so that Emblica officinalis can be clarified for its application in CINV as a potential candidate. Groups I, II, III, IV, and V rats were pretreated orally with 1% carboxymethyl cellulose (CMC, 1 mL/kg), 1% CMC (1 mL/kg), EEEO (250 mg/kg), EEEO (500 mg/kg), and ondansetron (3 mg/kg), respectively, for 5 consecutive days. Then, Group I rats received 0.1 mL of normal saline and Groups II–V rats received 10 mg/kg body weight of cisplatin intraperitoneally. Immediately after that, a test meal (1.5 mL/rat) was administered to each group, and after 30 minutes, rats were euthanized to evaluate the percentage of gastric emptying. EEEO at the specified doses reversed the cisplatin-induced delayed gastric emptying. EEEO (500 mg/kg body weight) pretreatment for 5 days before cisplatin challenge in Group IV rats significantly ( p < .05) increased gastric emptying to 74.25% ± 7.19%. Reversal of cisplatin-induced delay in gastric emptying by EEEO (500 mg/kg body weight) in Group IV was significantly ( p < .05) comparable to that of the ondansetron treated Group V. EEEO possesses the property to reverse the cisplatin-induced delayed gastric emptying and can be used as an antiemetic for the prevention of CINV.